A study on hygienic standard of food premises and microbiological quality of food in Kota Bharu - Abdullah, Mohamed Rusli; Ismail, Zaliha (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
A cross sectional study was carried out to determine the total plate count, coliform and E. coli counts in 712 selected foods sample taken from 362 food premises in the area under the Municipal Jwisdiction of Kota Bharu. The foods were classified according to the groups. Standard method were used to determine the total plate count (TPC in CFU/gm), coliform count (CC in :M:PN/ml) and E. coli count in ( MPN/ml). Microbiological analysis of food samples showed that 34.08% of sample had unsatisfactory in total plate count, 47.8% in coliform count and 24.7% in E. coli count. E. coli count was detected more in staple foods as compared to snacks/ kuih. There was a significant difference of the satisfactory levels of microbiological analysis amongst different groups of food (P<0.001). This study was found to have overall relationship between microbiological findings of selected food examination and the hygiene score of food premises. Appropriate measures, such as education of food handlers in improving the hygienic practice, particularly by environmental health officers, public health inspectors and local authorities are needed in order to reduce the prevalence of food borne diseases.